All Days 2015
DOI: 10.4043/25778-ms
|View full text |Cite
|
Sign up to set email alerts
|

Fiber Optic Sensor Based Monitoring System for Blowout Preventer

Abstract: Ultra-deep water BOP (Blowout Preventer) operation poses numerous challenges in obtaining accurate knowledge of current system integrity and component condition-a salient example is the difficulty of verifying closure of the pipe and shearing rams during and after well control events. Ascertaining the integrity of these functions is currently based on a manual volume measurement performed with a stop watch. Advances in sensor technology now permit more accurate methods of BOP condition monitoring. Fiber optic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 1 publication
0
1
0
Order By: Relevance
“…E. Hajidavalloo installed flow tubing at the wellhead and varied the size of the tubing to study its effect on the blowout flow rate [15]. A. Turner and P. Loustau use blowout preventers for blowout-related parameter measurements, which are fast and work consistently in complex environments [16]. M. D. Dunn predicted the blowout fluid flow velocity under freefield conditions and concluded that the jet velocity decreases with increasing jet height as the natural entrainment generated by air flows radially into the jet [17].…”
Section: Related Workmentioning
confidence: 99%
“…E. Hajidavalloo installed flow tubing at the wellhead and varied the size of the tubing to study its effect on the blowout flow rate [15]. A. Turner and P. Loustau use blowout preventers for blowout-related parameter measurements, which are fast and work consistently in complex environments [16]. M. D. Dunn predicted the blowout fluid flow velocity under freefield conditions and concluded that the jet velocity decreases with increasing jet height as the natural entrainment generated by air flows radially into the jet [17].…”
Section: Related Workmentioning
confidence: 99%